Theory of Malay Continuation Cultures - Nordin, Shah Rul Anuar (Human Sustainability Procedia, 2021)
Some books for instance Mental Revolution (1971) and The Malay Dilemma (1970) associated Malay community with negative traits, values and practices that could prevent them to prosper. They claimed as if this cultures still exist and embedded from previous generation to next generation. Hence, this paper aims to discuss this polemic through a qualitative design research using a content analysis approach. Research has found that a number of Malay scholars such as Syed Hussein Alatas, Zainal Abidin Ahmad, Senu Abdul Rahman and Taib Osman have discussed this issue in their books. Some of them said that the Malay community does have negative values and practices from generations to generation and some of them rejects this claim. The second group is more cautious and said that the Malays are not the only nation who behaving negatively as illustrated by the first group but it is a betrayal in manipulating the facts about the Malay community. The library research has led to a Theory of Malay Continuation Cultures.